Donkey skin: from text to context - Stakonski, Ana Carolina (2021)
This article analyzes the story Pele de asno, by Charles Perrault, seeking to understand childhood and sexuality configured in the historical context of the compilation of this production. The study showed that, in that context, even though there was an increasing questioning and disapproval of sexual activities between children and adults or practices such as incest, these were not uncommon and continued to be portrayed in the children’s stories. It should be noted that the perception built up until then about childhood was not at the heart of the concern with care based on moral and educational precepts such as those currently valued.